2013
DOI: 10.1093/rheumatology/ket148
|View full text |Cite
|
Sign up to set email alerts
|

Reduced joint assessment vs comprehensive assessment for ultrasound detection of synovitis in juvenile idiopathic arthritis

Abstract: The 10-joint PDUS assessment is valid and feasible for assessment of synovitis in JIA in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 19 publications
0
54
0
3
Order By: Relevance
“…The group agreed to examine 4 joints: knee, ankle, wrist, and second metacarpophalangeal (MCP) joint. Joint selection was based mainly on the fact that these are the most common peripheral joints involved in JIA (3,6). Since many MSUS publications focused on pediatrics have included the hip joint, we decided not to include it in the present study (7,8).…”
Section: Methodsmentioning
confidence: 99%
“…The group agreed to examine 4 joints: knee, ankle, wrist, and second metacarpophalangeal (MCP) joint. Joint selection was based mainly on the fact that these are the most common peripheral joints involved in JIA (3,6). Since many MSUS publications focused on pediatrics have included the hip joint, we decided not to include it in the present study (7,8).…”
Section: Methodsmentioning
confidence: 99%
“…An abundant number of studies have emerged in the literature over the past 2 decades for adult rheumatology, which included validation of the US detection of synovitis with histology and magnetic resonance imaging (MRI), standardization of the scanning technique, normative data acquisition, as well as documenting the responsiveness to change (11)(12)(13)(14)(15). These aspects have nevertheless only been partially addressed for pediatric patients (2,10,16); very few publications have started to collect information (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…There are several cohort studies that have shown that treatment of RA patients with TNFα antagonist results in significant improvement in disease when measured by ultrasound (27,3032). An evaluation of TNFα receptor antagonist efficacy in the treatment of RA patients revealed that the synovial color Doppler scoring of 28 joints was parallel to the changes in DAS28.…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of TNFα receptor antagonist efficacy in the treatment of RA patients revealed that the synovial color Doppler scoring of 28 joints was parallel to the changes in DAS28. Therefore, the ultrasonic inflammatory joints number and synovial color Doppler scoring was predictive of X-ray bone erosion (32). Scirè et al (33) performed a 2-year follow-up of 106 cases of early-stage RA patients, and showed that the exploration of color Doppler ultrasound towards the joint residual inflammation was much more sensitive than the clinical and laboratory indexes.…”
Section: Discussionmentioning
confidence: 99%